Evidence for a Holin-Like Protein Gene Fully Embedded Out of Frame in the Endolysin Gene of Staphylococcus aureus Bacteriophage 187 - Loessner, Martin J. (American Society for Microbiology, 1999)
We have cloned, sequenced, and characterized the genes encoding the lytic system of the unique Staphylococcus aureus phage 187. The endolysin gene ply187 encodes a large cell wall-lytic enzyme (71.6 kDa). The catalytic site, responsible for the hydrolysis of staphylococcal peptidoglycan, was mapped to the N-terminal domain of the protein by the expression of defined ply187 domains. This enzymatically active N terminus showed convincing amino acid sequence homology to an N-acetylmuramoyl-l-alanine amidase, whereas the C-terminal part, whose function is unknown, revealed striking relatedness to major staphylococcal autolysins. An additional reading frame was identified entirely embedded out of frame (+1) within the 5′ region of ply187 and was shown to encode a small, hydrophobic protein of holin-like function. The hol187 gene features a dual-start motif, possibly enabling the synthesis of two products of different lengths (57 and 55 amino acids, respectively). Overproduction of Hol187 in Escherichia coli resulted in growth retardation, leakiness of the cytoplasmic membrane, and loss of de novo ATP synthesis. Compared to other holins identified to date, Hol187 completely lacks the highly charged C terminus. The secondary structure of the polypeptide is predicted to consist of two small, antiparallel, hydrophobic, transmembrane helices. These are supposed to be essential for integration into the membrane, since site-specific introduction of negatively charged amino acids into the first transmembrane domain (V7D G8D) completely abolished the function of the Hol187 polypeptide. With antibodies raised against a synthetic 18-mer peptide representing a central part of the protein, it was possible to detect Hol187 in the cytoplasmic membrane of phage-infected S. aureus cells. An important indication that the protein actually functions as a holin in vivo was that the gene (but not the V7D G8D mutation) was able to complement a phage λ Sam mutation in a nonsuppressing E. coli HB101 background. Plaque formation by λgt11::hol187 indicated that both phage genes have analogous functions. The data presented here indicate that a putative holin is encoded on a different reading frame within the enzymatically active domain of ply187 and that the holin is synthesized during the late stage of phage infection and found in the cytoplasmic membrane, where it causes membrane lesions which are thought to enable access of Ply187 to the peptidoglycan of phage-infected Staphylococcus cells.